Polarimetric characterization of debris and faults in the highway environment at millimeter-wave frequencies. - Sarabandi, K. (IEEE Transactions on antennas and propagation)
In this paper, measurements and models for the polarimetric backscatter response of various paint targets on roads and road surface faults are presented. Of particular interest are debris and faults that could lead to fatal accidents and damage of property. A desired safety feature for automotive radar sensors is the capability of detecting such debris and faults. The detectability of a point target is evaluated by comparing its RCS value with the RCS threshold value defined by the backscatter response of the road surface. Extensive backscatter measurements at W-band were conducted to obtain the backscatter response of typical debris and faults on asphalt surfaces at near grazing incidence angles (76°-86°). On the other hand, theoretical models, based on diffraction from impedance wedges and scattering from impedance cylinders, respectively, as well as physical optics approximation, were developed to predict the backscatter response of road surface faults and targets with planar facets on road surfaces. Experimental results indicate that detectability in all cases is a function of target size, its azimuthal angle with respect to radar boresight, and the polarization state of the system. The measured backscatter response is used to verify the validity of the theoretical models. Angular polarimetric backscatter measurements of targets defining roadside boundaries such as a concrete curb, a guardrail, and a pebble surface are also presented. The results of these measurements could be used to alert fatigued drivers should their vehicles be heading sideward